A COVID‐19‐ready public health surveillance system: The Food and Drug Administration's Sentinel System - Cocoros, Noelle M.; Fuller, Candace C.; Adimadhyam, Sruthi; Ball, Robert; Brown, Jeffrey S.; Dal Pan, Gerald J.; Kluberg, Sheryl A.; Lo Re, Vincent; Maro, Judith C.; Nguyen, Michael; Orr, Robert; Paraoan, Dianne; et al. (Pharmacoepidemiology and drug safety, 2021)
The US Food and Drug Administration's Sentinel System was established in 2009 to use routinely collected electronic health data for improving the national capability to assess post‐market medical product safety. Over more than a decade, Sentinel has become an integral part of FDA's surveillance capabilities and has been used to conduct analyses that have contributed to regulatory decisions. FDA's role in the COVID‐19 pandemic response has necessitated an expansion and enhancement of Sentinel. Here we describe how the Sentinel System has supported FDA's response to the COVID‐19 pandemic. We highlight new capabilities developed, key data generated to date, and lessons learned, particularly with respect to working with inpatient electronic health record data. Early in the pandemic, Sentinel developed a multi‐pronged approach to support FDA's anticipated data and analytic needs. It incorporated new data sources, created a rapidly refreshed database, developed protocols to assess the natural history of COVID‐19, validated a diagnosis‐code based algorithm for identifying patients with COVID‐19 in administrative claims data, and coordinated with other national and international initiatives. Sentinel is poised to answer important questions about the natural history of COVID‐19 and is positioned to use this information to study the use, safety, and potentially the effectiveness of medical products used for COVID‐19 prevention and treatment.